Mandatory Basic Life Support Training: Why NOT In India; Mandatory End-of-Life Care Policy: Why NOT In India; Mandatory Medical Research Requirements: Why SO In India! - Gupta, Deepak (Indian Journal of Community Health, 2017)
In the world of things and doings, mandatory is a human invention for the times when optional and free-will do NOT get things done. When quality of life gains momentum to catch on with the age-old run for quantity of life, the medical education, medical decision-making and medical policy-making do NOT leave an option for medical practitioners but to follow the mandate as required and warranted by society they cater for. Herein I want to review and discuss some of those potential mandates for practitioners of medicine from the perspective of (a) a person who can be in the hot seat of a patient himself, (b) a physician who can be caught in the dubious scenarios of treating patients similar to himself, and (c) a medical teacher-researcher who till recently as an inquisitive medical student was himself delving with similar questions for the system. In a nutshell, this is my perspective from my limited understanding that basic life support (BLS) training and end-of-life care (EOLC) policy are in need for mandate to being made mandatory whereas medical research requirements (MRR) are in need to be made optional without covert-overt penalties.